2019
DOI: 10.31018/jans.v11i3.2158
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air pollution of PM2.5 in urban households of Jammu, (J&K)

Abstract: The rising problem of Respirable Particulate Matter i.e. PM2.5 and smaller is catching attention of the policymakers, stakeholders as well as common man. The study of the IndoorPM2.5 of the particular area is very important as it is having direct impact on the human health because PM2.5is absorbed into lung alveolar tissues during breathing and causes respiratory and cardiovascular problems. In present study attempt has been made to assess the status of Indoor PM2.5 in Urban Households of Jammu, (J&K). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The critical analysis of data at Commercial area revealed that values of PM2.5 were highest in CTC followed by CLWE and least in CLIM whereas the values of PM1.0 were highest in CTC followed by CLE and least by CLIM, PM0.50 were highest in CTC followed by CLIE and least by CLE and PM0.25 were found highest in CTC followed by CLWE and least by CLIE households (figure 4). These results support the findings of Nishu and Rampal (2019) that in comparison to residences even without exhaust, Chulha-using households showed higher levels of indoor PM2.5 at all the study sites. Further, the analysis of the data of particulate matter in the households with traditional chullah revealed that kitchens of residential area exhibited insignificantly (p>0.05) higher values of PM2.5, PM1.0, PM0.50 and PM0.25 as compared with that of commercial area.…”
Section: Resultssupporting
confidence: 90%
“…The critical analysis of data at Commercial area revealed that values of PM2.5 were highest in CTC followed by CLWE and least in CLIM whereas the values of PM1.0 were highest in CTC followed by CLE and least by CLIM, PM0.50 were highest in CTC followed by CLIE and least by CLE and PM0.25 were found highest in CTC followed by CLWE and least by CLIE households (figure 4). These results support the findings of Nishu and Rampal (2019) that in comparison to residences even without exhaust, Chulha-using households showed higher levels of indoor PM2.5 at all the study sites. Further, the analysis of the data of particulate matter in the households with traditional chullah revealed that kitchens of residential area exhibited insignificantly (p>0.05) higher values of PM2.5, PM1.0, PM0.50 and PM0.25 as compared with that of commercial area.…”
Section: Resultssupporting
confidence: 90%